The association between maternal factors and milk hormone concentrations: a systematic review - Qureshi, Raabiah; Fewtrell, Mary; Wells, Jonathan C. K.; Dib, Sarah (Frontiers in Nutrition, 2024)
Background: Breast milk is the gold standard for infant feeding. It is a dynamic biological fluid rich in numerous bioactive components. Emerging research suggests that these components, including hormones, may serve as signals between mother and offspring. From an evolutionary perspective, maternal hormonal signals could allow co-adaptation of maternal and offspring phenotype, with implications for their Darwinian fitness. However, a series of steps need to be considered to establish the role of a component as a signal and this systematic review focuses on one step: 'Do maternal factors influence the concentration of milk hormones?'.Objective: To systematically review human studies which analyse the association between maternal factors and the concentration of hormones in breast milk.Methods: Three databases were searched for studies reporting the association of maternal factors including body mass index (BMI), weight, fat mass, age, ethnicity, smoking with hormones such as adiponectin, leptin, insulin, ghrelin, and cortisol in breast milk.Results: Thirty-three studies were eligible for inclusion. Maternal BMI was positively associated with milk leptin (20/21 studies) and with milk insulin (4/6 studies). Maternal weight also displayed a positive correlation with milk leptin levels, and maternal diabetes status was positively associated with milk insulin concentrations. Conversely, evidence for associations between maternal fat mass, smoking, ethnicity and other maternal factors and hormone levels in breast milk was inconclusive or lacking.Conclusion: Current evidence is consistent with a signalling role for leptin and insulin in breast milk, however other steps need to be investigated to understand the role of these components as definitive signals. This review represents a first step in establishing the role of signalling components in human milk and highlights other issues that need to be considered going forward.